The Role of Audit in Detecting Errors in Financial Statements - Kastrati, Agim (European Journal of Economics and Business Studies, 2015)
The main objective of the audit is to detect potential errors in the client’s financial statements. This study aims to identify faults that are detected by auditors during auditing of financial statements. Ten audit firms are interviewed, in various cities of Kosovo, for the purpose of collecting data for errors found during the audit of the financial statements of their clients, for the period January-December 2012. The data obtained show that through the implementation of various audit procedures are found different type of errors which occur for various reasons ranging from lack of experience of clients personnel, insufficient knowledge of accounting principles and negligence. Data from this study provide empirical support to previous studies. Researches undertaken by Hylas and Ashton (1982) have shown that the audit affects the detection of errors in the financial statements, which have occurred for various reasons. The study provides knowledge that audit helps companies to eliminate errors which affect the accuracy and reliability of financial statements.